UPAYA PEMERINTAH KOTA TEGAL DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD)MELALUI SEKTOR PERIKANAN - GEMILANG DWI ANANDIKA, AMIEK SOEMARMI, HENNY JULIANI (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Tegal has marine natural resources and huge potential as a source of income for local finances in an effort to increase revenue, the government is expected could has role authority as the executor of the exploration and management of marine resources should be able to explore the potential of marine and fisheries sector in order to optimizing the implementation of regional autonomy. The method that used the juridical empirical approach. Which is to analyze the implementation of legislation Number 3 Year 2010 concerning levies and Perwal Fish Auction No.31 of 2010 on the Implementation Operation Levy fish auction. The specifications of the research was supported by the descriptive analysis of primary data and secondary data. Then analyzed by the data in the field whether in or not appropriate requirements prescribed, and it performed with qualitative analysis aswen. The results showed that one source of Tegal revenue comes from levies Tegal fish auction to the implementation of Tegal Regulation Number 3 Year 2010 on Implementation and Retribution TPI. The legal basis for the regulation is made ​​of PP No.38 of 2007 on Government Affairs Division of the Government, Provincial Government and the Government of Regency / City. Applicability of Regulation 3 Tegal 2010. Data obtained from 2009 to 2011 through the contribution of the fisheries sector and local cash income increased. Proven to up levy fee of 0.95% to 2.78%, and therefore the government is expected to completing the facility in the implementation of the fisheries sector levy collection to run according to the rules and avoiding violations.